Analisis Sistem Informasi Pengolahan Data Bahan Makanan Kering (BMK) Di Gudang Instalasi Gizi Rumah Sakit PKU Muhammadiyah Surakarta - Handayaningrum, Nuroini, Dwi Astuti, SKM., M.Kes, Sri Darnoto S.KM M.PH (2014)
PKU Muhammadiyah Hospital in Surakarta is a mobile plant in the field of health, effective health service factors and quality is the aim of the installation. In making report of dry food ingredients, PKU Muhammadiyah Hospital in Surakarta develop information systems data processing dry food ingredients (BMK). This study aims to describe the information systems data processing dry food ingredients in PKU Muhammadiyah Hospital in Surakarta. The analysis was performed to determine the description of the information system, the method comprising PIECES analysis: Performance, Information, Economy, Control, Efficiency and Service. The results showed the presence of data processing information systems dry groceries online, the better the performance of the officer, the information generated on time, report generation becomes more efficient, security and supervision can be controlled, the officer can work optimally and the system is far better than the system the manual.